An alternating current impedance study of polypyrrole/poly(vinyl chloride) composites - Waller, A; Hampton, A; Compton, R (1989)
A.c. impedance studies of poly(vinyl chloride)-polypyrrole composites deposited on platinum electrodes and in contact with an acetonitrile solution containing 0.1 mol dm-3 tetrabutylammonium tetrafluoroborate (as supporting electrolyte) are described. Data are presented for the frequency range 0.1 Hz-65 kHz, and in this way the conductivity of the composite is found. The latter is related to the potential applied via the platinum electrode to the composite, and to the amount of polypyrrole incorporated within the composite. In-situ electrochemical e.s.r. measurements on the composite are also described, and these, together with the a.c. data, indicate the electrical properties and behaviour of the composite material to be similar to polypyrrole itself.